Improving resilience in rainfed and irrigated agriculture under future climate in the winter rainfall region of the Western Cape : lessons from the 2015-2018 drought - Theron, Simone (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhDAgric)--Stellenbosch University, 2022.